The ethics of entrepreneurship: a Millian approach - Cordasco, Carlo Ludovico (Journal of business ethics, 2024)
What is morally valuable - if anything at all - in entrepreneurship? Existing normative takes can be broadly categorized as belonging to two main views: a backward and a forward-looking approach. The former sees entrepreneurial activity as a permissible emergent product of individuals' interactions within the boundaries of people's existing rights; the latter looks at entrepreneurship in the broader context of market processes and emphasizes its role in generating Pareto-improvements in social welfare. In this paper, I suggest that certain instances of entrepreneurship can be intrinsically valuable when they constitute Millian Experiments in Living, that is when entrepreneurial ventures are the expression of an entrepreneur's conception of the good. Engaging in entrepreneurial activity which reflects one's conception of the good helps individuals in cultivating their individuality and originality by means of subjecting their normative beliefs to empirical scrutiny, thus allowing one to confirm, revise, or refine them.